Penerapan Gaya Belajar Akomodator dan Asimilator Pada Pembelajaran Kewirausahaan Untuk Menumbuhkan Semangat Wirausaha Mahasiswa Program Studi Pendidikan Ekonomi FPIPS IKIP PGRI Bojonegoro - Eka Farida; Sarjono Sarjono (Universitas Hamzanwadi, 2018)
Entrepreneurship learning becomes relevant to the problem of educated unemployment which has increased from year to year because the paradigm that after completing the study must be a job seeker. The application of an accommodator learning style and assimilation in learning entrepreneurship can foster the spirit of student entrepreneurship. The purpose of this study was to measure student learning styles into accommodating and assimilation learning style groups, and test the effect of entrepreneurial learning based on learning styles on student entrepreneurial enthusiasm. The research method used is ex-post facto experimental and explanatory. The results of the study included most students who had appropriate learning styles, portfolio assessments showed very good and good grades, students who had taken entrepreneurial learning had a good entrepreneurial spirit, and the t test showed that entrepreneurship learning had an influence on students' entrepreneurial spirit. with the value of R2 12.1% with a significance level of 0.037%